Gestão e percepção ambiental : a área de proteção ambiental Morro do Urubu - Aracaju (SE) - Matos, Anselmo Araújo (2010)
To growing world concern with the environment starting from the decade of 60, culminated with the institutional of administration mechanisms and environmental protection, that in Brazil was unchained through the creation of Units of Conservation (UC) found in the National Politics of the Environment (PNMA). However, the administration problems related to UC's created in Brazil previous to the National System of Units of Conservation (SNUC) they occur of the absence of the popular participation in the creation discussions, that were almost always summarized to the ordinance that to it instituted them, without creating subsidies to guarantee his administration and their objectives. In that way this study aimed at to analyze how it is happening the planning and administration of the Area of Environmental Protection (APA) I Die from the Vulture legally constituted since 93, being taken as point of reference the law of SNUC. For that, as specific objectives they were analyzed the perception on the social actors' APA involved directly and indirectly in the administration of the area such an as residents and public managers with the purpose of analyzing their environmental perceptions and the respective impediments for the administration of the area. This analysis felt through the application interviews the residents of the neighborhood Porto Dantas and the managers that of some form has performance in the study area semi-structured close to. However, these interviews emphasized a deep absence of knowledge of the population in relation to APA checking them a dissociated perception of the environmental subjects, in the same way, the managers demonstrated a complete to disarticulate among the public institutions with performance in the area, what emphasizes his without it manages, disregard and disrespect the effective environmental legislation.